Association between circulating levels of C-reactive protein and positive and negative symptoms of psychosis in adolescents in a general population birth cohort. (November 2021) - Khandaker, Golam M.; Stochl, Jan; Zammit, Stanley; Lewis, Glyn; Dantzer, Robert; Jones, Peter B.
Abstract: Background: Schizophrenia is associated with elevated levels of circulating C-reactive protein (CRP) and other inflammatory markers, but it is unclear whether these associations extend to psychotic symptoms occurring in adolescence in the general population. A symptom-based approach may provide important clues for apparent trans-diagnostic effect of inflammation, which is also associated with depression and other psychiatric disorders. Methods: Based on data from 2421 participants from the Avon Longitudinal Study of Parents and Children birth cohort, we examined associations of serum CRP levels assessed around age 16 with ten positive and ten negative symptoms of psychosis assessed using questionnaires around age 17, using both individual symptoms and symptom dimension scores as outcomes. Regression models were adjusted for sex, body mass index, depressive symptoms, substance use, and other potential confounders. Results: Most prevalent positive symptoms were paranoid ideation (4.8%), visual (4.3%) and auditory (3.5%) hallucinations. Negative symptoms were more strongly correlated with concurrent depressive symptoms ( r= 0.51; P < 0.001) than positive symptoms ( r pb = 0.19; P < 0.001). The associations of CRP with positive and negative symptom dimension scores were similar. At individual symptom level, after adjusting for potential confounders including depressive symptoms, CRP was associated with auditory hallucinations (adjusted OR = 2.22; 95% CI, 1.04–4.76) and anhedonia (adjusted OR = 1.13; 95% CI, 1.02–1.26). Conclusions: Inflammation is associated with sub-clinical psychotic symptoms in young people in general population. Association of CRP with symptoms commonly shared between mood and psychotic disorders, such as auditory hallucinations and anhedonia, could be one explanation for the apparent trans-diagnostic effect of inflammation. Highlights: We examined psychotic symptoms in adolescents from a population-based birth cohort. Common positive symptoms were paranoid ideation, visual and auditory hallucinations. Negative symptoms were correlated with depressive and positive symptoms. CRP was similarly associated with positive and negative symptom dimension scores. CRP was specifically associated with auditory hallucinations and anhedonia.